Doppler sonographic evaluation of intrauterine growth restriction of fetus and its correlation with perinatal outcomes among the population of riverine (char) areas of Barpeta Assam - Ullah, Ibrahim K.; Thakur, Madhurjya K.; Varma, Dixit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Intrauterine growth restriction (IUGR) also known as fetal growth restriction (FGR), has been associated with a variety of detrimental perinatal outcomes. FGR is defined as estimated fetal weights (EFW) or abdominal circumference (AC) that fall within the third, or tenth percentiles with abnormal doppler parameters. FGR affects 10-15% of all pregnancies around the world. Methods: Prospective observational study of singleton pregnant women complicated by FGR were enrolled during the study period from September 2021 to August 2022. 100 patients were included in the study. Results: Abnormal umbilical artery flow was seen in 30% of cases, out of which 83% (25) had abnormal perinatal outcome. Out of 100 cases, live births were reported in 94%, stillbirths in 4%, and IUDs in 2%. There were 16 neonatal deaths and 15 neonatal complications among the adverse perinatal outcomes. Intraventricular hemorrhage and neonatal sepsis were the two leading causes of death. Neonatal sepsis, necrotizing enterocolitis and hypoxic ischemic injury was the leading cause of morbidity. Reverse end diastolic umbilical artery Doppler and bilateral uterine artery notch had 100% mortality. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of umbilical artery in predicting perinatal outcome in IUGR were 80.65%, 92.75%, 83.33% 91.43% and 89.47% respectively. Conclusions: Umbilical artery PI is the most sensitive parameter and had highest positive and negative predictive value and Accuracy in relation to adverse perinatal outcomes.